(untitled) (Critical Romani Studies, 2020)
This article investigates the invisibility of Roma communities within Scottish census ethnic monitoring categories and broader empirical data. Consistent negative stereotyping as well as systematic oppression within social policy, dominant discourses, and data collection processes excludes Roma from participatory citizenship. This article identifies precise forms of marginality and invisibility within official government data – permeated through social and education policy – that thereby limit the effective targeting of resources to marginalized communities. Specifically, the article argues that omitting Roma as an ethnic category from past data gathering processes limits understanding of the commonalities and differences within and among Scottish communities, rendering entire populations invisible within broader empirical data and therefore restricting both identification of needs and effective resource allocation. Thus, the article presents a timely argument for the inclusion of Roma as an ethnic category in the 2021 Scottish census, while addressing issues within the census approach to data collection – including the impending digitization of the process. Through discussing and advancing the case for the inclusion of Romani communities in the 2021 Scottish Census, the paper also seeks to establish the current social context by chronicling the history of Romani migration and marginalization within Europe.